Identifikasi Jenis Pohon pada Hutan Kota Alun-Alun Kabupaten Polewali mandar - Sabri, Akbar Sabri; Farid Karim, Faradilah (Pangale Journal of Forestry and Environment, 2023)
Urban forests function effectively as climate controllers, including functioning as lowering temperature, absorbing solar radiation, and breaking wind flow. The selection of potential tree species with regional typologies and their designation for urban forest development is an effort to reduce these negative impacts. The purpose of this study was to identify the diversity of tree species in the urban forest of Polewali Mandar Regency Square. This research was conducted in March-May 2023 in the town square area of Polewali Mandar Regency. The research method is the census method, namely by recording all types and number of trees that grow above the ground. There were 8 plots with the size of each plot of 20 m x 20 m. The results showed that there were 14 types of trees in the city forest area of Polewali Mandar Regency consisting of 9 families. Ketapang Kencana (Terminalia mantaly) is a tree species that has the highest importance index value of 109.46%. The tree diversity index value is 1.299% which is in the medium category